The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1001/jamaophthalmol.2022.3778
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Parental Leave and Ophthalmology Resident Physician Performance

Abstract: ImportanceAlthough parental leave is essential in enhancing resident wellness and fostering inclusive workplace environments, residents may often feel discouraged from using parental leave owing to perceived stigma and concerns about possible negative effects on their training.ObjectiveTo examine parental leave usage across multiple institutions and compare residency performance metrics between residents who took parental leave vs their peers who did not take leave.Design, Setting, and ParticipantsThis was a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…33 While the m-quotient does not account for parental leave, a study of ophthalmology residents in the United States found no significant differences in parental leave duration by gender. 34 In our study, a sevenfold increase in the proportion of women was found when comparing periods 1942 to 1961 and 2002 to 2021. Meanwhile, from 1938 to 1997, no more than one women board president was found among all Canadian and American societies analyzed.…”
Section: Discussionsupporting
confidence: 46%
“…33 While the m-quotient does not account for parental leave, a study of ophthalmology residents in the United States found no significant differences in parental leave duration by gender. 34 In our study, a sevenfold increase in the proportion of women was found when comparing periods 1942 to 1961 and 2002 to 2021. Meanwhile, from 1938 to 1997, no more than one women board president was found among all Canadian and American societies analyzed.…”
Section: Discussionsupporting
confidence: 46%
“…A study of physical medicine and rehabilitation residents showed no difference in board certification exam passing rates among individuals who took a medical or parental leave [27]. A study of ophthalmology residents who took parental leave found no differences in average scores on standardized assessments, research activity, ACGME milestone scores, or surgical volumes [28]. Additional studies in neurology residency are needed to understand if time away from neurology residency objectively impacts clinical training.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Use of currently available family leave, lactation support, and return-to-work resources is dismal in medicine. [4][5][6] This stems from multiple factors including traditionally inflexible schedules, expectation of long work hours, and hierarchical structures of academic medicine. 7,8 In fact, young physician parents must often use all vacation days before requesting time off after childbirth/adoption.…”
Section: Introductionmentioning
confidence: 99%